Calcium-induced stabilization of α-amylase against guanidine hydrochloride denaturation - Tan, Cheau Yuaan; Raja Abdul Rahman, Raja Noor Zaliha; Abdul Kadir, Habsah; Tayya, Saad (Academic Journals, 2010)
Guanidine hydrochloride (GdnHCl) denaturation of native and Ca-depleted Bacillus licheniformis α-amylase (BLA) was investigated both in the absence and presence of 2 mM calcium chloride (CaCl2)using circular dichroism, fluorescence spectroscopy and biological activity. In both states (Cadepleted and native form), the protein was denatured to a considerable extent in the absence of 2 mM CaCl2 with concomitant loss of biological activity upon increasing GdnHCl concentration. On the other hand, this effect was significantly reduced when 2 mM CaCl2 was included in the incubation mixture as revealed by a higher relative mean residue ellipticity, higher relative fluorescence intensity, smaller change in emission maximum and lesser reduction in biological activity. Interestingly, using these probes, 2 mM CaCl2 seemed to offer the same degree of stability to Ca-depleted BLA as that observed with native BLA in the absence of 2 mM CaCl2. All these results suggest calcium-induced stabilization of BLA against GdnHCl denaturation.